Assessment of background concentrations of organometallic compounds (methylmercury, ethyllead and butyl- and phenyltin) in French aquatic environments. (1st May 2016) - Cavalheiro, Joana; Sola, Cristina; Baldanza, Julie; Tessier, Emmanuel; Lestremau, François; Botta, Fabrizio; Preud'homme, Hugues; Monperrus, Mathilde; Amouroux, David
Abstract: The aim of this work is to estimate background concentrations of organometallic compounds, such as tributyltin (TBT), dibutyltin (DBT), monobutyltin (MBT), triphenyltin (TPhT), diphenyltin (DPhT), monophenyltin (MPhT), methylmercury (MeHg), inorganic mercury (iHg) and diethyllead (Et2 Pb) in the aquatic environment at the French national scale. Both water and sediment samples were collected all over the country, resulting in 152 water samples and 123 sediment samples collected at 181 sampling points. Three types of surface water bodies were investigated: rivers (140 sites), lakes (19 sites) and coastal water (42 sites), spread along the 11 French river basins. The choice of sites was made on the basis of previous investigation results and the following target criteria: reference, urban sites, agricultural and industrial areas. The analytical method was properly validated for both matrices prior to analysis, resulting in low limits of quantification (LOQ), good precision and linearity in agreement with the Water Framework Directive demands. The results were first evaluated as a function of their river basins, type of surrounding pressure and water bodies. Later, background concentrations at the French national scale were established for both water and sediment matrices, as well as their threshold, i.e., the concentration that distinguishes background from anomalies or contaminations. Background concentrations in water are ranging between <0.04–0.14 ng Hg. L −1 for MeHg, <0.14–2.10 ng Hg. L −1 for iHg, <1.0–8.43 ng Pb. L −1 for Et2 Pb and 0.49–151 ng Sn. L −1, <0.08–3.04 ng Sn. L −1 and <0.08–0.25 ng Sn. L −1 for MBT, DBT and TBT, respectively. For sediments, background concentrations were set as <0.09–1.11 ng Hg. g −1 for MeHg, <0.06–24.3 ng Pb. g −1 for Et2 Pb and <1.4–13.4 ng Sn. g −1, <0.82–8.54 ng Sn. g −1, <0.25–1.16 ng Sn. g −1 and <0.08–0.61 ng Sn. g −1 for MBT, DBT, TBT and DPhT, respectively. TBT occurs in higher concentrations than the available environmental protection values in 24 and 38 sampling sites for both water and sediment samples, respectively. Other phenyltins (MPhT and TPhT) did not occur above their LOQ and therefore no background was possible to establish. Throughout this work, which is the first assessment of background concentrations for organometallic compounds at the French national level ever being published, it was possible to conclude that over the last 10–20 years organotin concentrations in French river basins have decreased while MeHg concentration remained stable. Graphical abstract: Highlights: First assessment of background concentrations for organometallic compounds in France. Water (152 samples) and sediment samples (123) were collected all over the country. The analytical method was properly validated for both matrices prior to analysis. The results reveal an overall decreasing on organotin concentrations in French river basins. Concentrations for mercury species remain stable over time.